Developing C2-Aroyl Indoles as Novel Inhibitors of IDO1 and Understanding Their Mechanism of Inhibition via Mass Spectroscopy, QM/MM Calculations and Molecular Dynamics Simulation - Chauhan, Jyoti; Maddi, Srinivas R.; Dubey, Kshatresh Dutta; Sen, Subhabrata (Frontiers in Chemistry, 2021)
Indoleamine-2,3-dioxygenase (IDO1) and tryptophan dioxygenases are two heme based metalloenzymes that catalyze the tryptophan oxidation reaction by inserting molecular dioxygen to cleave the pyrrole ring. The mechanism of such ring cleavage reaction is of carcinogenic importance as the malignant tumors recruit this mechanism for immune invasion. In the presence study, we have synthesized a Novel C2 aroyl indoles inhibitor, 8d, which shows significant inhibition of 180 nM at IC50 scale. The binding and conformational changes that transpire after inhibitor binding were thoroughly studied by molecular docking and MD simulations. The subsequent QM/MM (Quantum Mechanical/Molecular Mechanical) calculations were used to proposed the mechanism of inhibition. The QM/MM calculations show that the reaction proceeds via multistep processes where the dioxygen insertion to the substrate 8a is the rate determining process. Theoretical mechanism is further supported by mass spectroscopy, and drug metabolism/pharmacokinetics study (DMPK) and metabolic stability of compound 8d was investigated in rat and human liver microsomes.